Overview Of Asean Environment, Transboundary Haze Pollution Agreement And Public Health - Nazeer, Nazia; Furuoka, Fumitaka (Penerbit Universiti Sains Malaysia (USM Press), 2017)
The hazardous consequences of haze and fires compelled the ten fellow countries of ASEAN to conclude a historic regional agreement on transboundary haze pollution to confront this problem. This paper provides an overview of ASEAN environmental conditions, the failure of the Transboundary Haze Pollution Agreement, and the adverse effects of its failure on public health. The study argues that there is a potential in the region to overcome the haze problem; although the ASEAN haze agreement lacks enforceable obligatory provisions, it remains a beneficial vehicle for regional cooperation to eradicate transboundary pollution.